Autumn waterbird migration over Lake Superior: Numbers, species, and timing - Youngman, Joseph A.; Flaspohler, David J.; Knowlton, Jessie L.; Dombroski, Louis J. (Journal of Great Lakes Research, 2017)
© 2017 International Association for Great Lakes Research The Great Lakes are used as a migratory corridor and for feeding by tens of thousands of waterbirds each spring and fall, yet little species-specific information is available regarding numbers, seasonal timing, and connectivity along the route. The objective of this study was to use land-based surveys to quantify fall migration at two important landmarks in Lake Superior for an assemblage of waterbirds from three orders (Anseriformes, Gaviiformes, and Podicipediformes). Both the Keweenaw Peninsula (KP) and Whitefish Point (WP) showed a temporal pattern of high numbers (peaking at 9000 and 16,000, respectively) in the first 3 h after dawn and a decline (dropping to 1000 and 5000, respectively) over the following 5 h, although the decline was far more abrupt at KP than at WP. Fall totals for WP were nearly 85,000 individual waterbirds, and for KP about 34,500. Species abundance rankings were generally similar for both locations, with the most common species being long-tailed duck (Clangula hyemalis), red-necked grebe (Podiceps grisegena), greater scaup (Aythya marila), and red-breasted merganser (Mergus serrator). Most species were far more numerous at WP than at KP, with long-tailed ducks being 65 times more numerous. A notable exception was redhead (Aythya americana), which was 33% more numerous at KP than at WP. We suggest that during the fall, Lake Superior acts as a geographic funnel concentrating waterbirds from northwest to southeast and that details of the composition, timing and amplitude of this phenomenon are important considerations for any nearshore Great Lakes development.